(untitled) (Economic and Political Thought, 2016)
The article analyses the characteristic features of military threats from Russia to the northern and eastern flanks of NATO. The starting points are first of all the direction and objectives of modernisation and development of the Russian military forces, Russian military exercises and possible strategic aims of the expansive policy of Moscow in the Baltic region. Next, the threat is analysed through the prism of three concepts that have appeared in the scientific and public debate in the context of Russia’s aggressive policy: a hybrid war, a strategic military surprise and a limited war. Making conclusions, the author states that on no account NATO should treat hybrid operations as a basic scenario of potential aggression by Russia. Such a treat, although real, is neither more probable nor the most dangerous from the point of view of negative results as well as the possibility of defending against them. The biggest challenge that NATO and such countries as Poland are facing is undertaking steps to protect the eastern flank of the alliance against unexpected conventional military aggression.